Strategi Komunikasi dalam Keluarga Antar Suku Jawa-Dayak di Kota Palangka Raya - Junaidi Junaidi; Aquarini Aquarini; Nauliana Nauliana (Anterior Jurnal, 2019)
Communication Strategy is planning and management for a purpose with effective communication in it. This research will explain and describe the Communication Strategies in the Java-Dayak Family in the City of Palangka Raya. The study entitled "Communication Strategies in Javanese-Dayak Family in Palangka Raya" is based on three indicators of intercultural communication, namely perception, Verbal process and Nonverbal process. The three indicators above must be owned by every family with different ethnic groups. This research uses a qualitative research approach. This qualitative research approach aims to explain the deepest phenomena. In qualitative research do not prioritize the size of the population or sampling even the population or sampling is very limited. Of the three indicators, indicators of perception and verbal processes are said to have been effective because the results of research on several families can learn, understand and adopt the culture of couples and apply in daily life both between husband and wife, and between parents to children. In the nonverbal process indicator, it seems that in one family under study it is less effective and creates an uncomfortable atmosphere in intercultural communication within the family. With this research, it is expected that later it can become a new science in communication references in families that have different ethnic groups in it.